Antifungal Susceptibility Profiles and Resistance Mechanisms of Clinical Diutina catenulata Isolates With High MIC Values - Chen, Xin-Fei; Zhang, Wei; Fan, Xin; Hou, Xin; Liu, Xiao-Yu; Huang, Jing-Jing; Kang, Wei; Zhang, Ge; Zhang, Han; Yang, Wen-Hang; Li, Ying-Xing; Wang, Jin-Wen; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Diutina catenulata (Candida catenulata) is an ascomycete yeast species widely used in environmental and industrial research and capable of causing infections in humans and animals. At present, there are only a few studies on D. catenulata, and further research is required for its more in-depth characterization and analysis. Eleven strains of D. catenulata collected from China Hospital Invasive Fungal Surveillance Net (CHIF-NET) and the CHIF-NET North China Program were identified using matrix-assisted laser desorption ionization–time of flight mass spectrometry and internal transcribed spacer sequencing. The antifungal susceptibility of the Diutina catenulata strains was tested using the Clinical and Laboratory Standards Institute broth microdilution method and Sensititre YeastOne™. Furthermore, ERG11 and FKS1 were sequenced to determine any mutations related to azole and echinocandin resistance in D. catenulata. All isolates exhibited low minimum inhibitory concentration (MIC) values for itraconazole (0.06–0.12 μg/mL), posaconazole (0.06–0.12 μg/mL), amphotericin B (0.25–1 μg/mL), and 5-flucytosine (range, < 0.06–0.12 μg/mL), whereas four isolates showed high MICs (≥ 4 μg/mL) for echinocandins. Strains with high MIC values for azoles showed common ERG11 mutations, namely F126L/K143R. In addition, L139R mutations may be linked to high MICs of fluconazole. Two amino acid alterations reported to correspond to high MIC values of echinocandin, namely F621I (F641) and S625L (S645), were found in the hot spot 1 region of FKS1. In addition, one new amino acid alteration, I1348S (I1368), was found outside of the FKS1 hot spot 2 region, and its contribution to echinocandin resistance requires future investigation. Diutina catenulata mainly infects patients with a weak immune system, and the high MIC values for various antifungals exhibited by these isolates may represent a challenge to clinical treatment.